CO 2 abatement opportunity in the UK through fuel-switching under the EU ETS (2005–2008): evidence from the E-Simulate model. (1st January 2011) - Lujan, Emeric; Delarue, Erik; Chevallier, Julien; D'haeseleer, William
The creation of the EU ETS led to changes in the merit order of the different plants competing on the electricity grid, and in the fuel-switching opportunities in the UK. This country has the greatest potential for CO 2 emissions reduction through fuel-switching within the EU, thanks to its suitable energy mix (39% of coal and 36% of natural gas in 2007). Through the modelling of the UK power system with the E-Simulate model, our central contribution documents that fuel-switching did occur in the UK as a consequence of the EU ETS: 20.1 Mton in 2005, 7.8 Mton in 2006, 0.52 Mton in 2007, and 14.3 Mton in 2008. We assess the relative contribution of different factors (carbon price, fuel prices and load in the power sector) to CO 2 emissions abatement by disentangling the impacts coming from the EU ETS, relative fuel prices variation, and with a 'switching band' analysis.